Standarisasi Halal Majelis Ulama Indonesia dalam Penyembelihan Ayam di Desa Kertawinangun Cirebon - Afif Muamar; Juju Jumena (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
This study aims to determine the process of slaughtering broilers in the village of Kertawinangun and the process of slaughtering according to the the Indonesian Ulema Council standard. This research is descriptive-analytical using qualitative methods. This research resulted in three things, first, the method of slaughtering and processing stages of broilers grouped into three stages, namely the stages in the preparation of chickens, slaughtering, and processing of chickens. And secondly, several factors influence consumer behavior related to halal slaughter, namely; 1) Cultural Factors, namely human behavior is largely determined by the culture that surrounds it, and its influence will always change every time by the times. 2) Social factors include family groups and role models. 3) Personal factors consisting of age and stages of the life cycle, economic conditions, lifestyle, and personality.